2021
DOI: 10.1002/jcb.29909
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline as an inhibitor to the SARS‐CoV‐2

Abstract: The coronavirus severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) remains an extant threat against public health on a global scale. Cell infection begins when the spike protein of SARS‐CoV‐2 binds with the human cell receptor, angiotensin‐converting enzyme 2 (ACE2). Here, we address the role of tetracycline as an inhibitor for the receptor‐binding domain (RBD) of the spike protein. Targeted molecular investigation show that tetracycline binds more favorably to the RBD (−9.40 kcal/mol) compared to do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Gendrot and collaborators employed the IHUMI-3 strain for which genomic data are not available, thus making it difficult to establish the degree of widespread of the virus and its comparison with other strains. Our SPR data indicated that doxycycline did not interact with relevant binding sites of S or ACE2 proteins, as instead suggested by an in silico study [ 15 ]. It cannot be excluded that it may affect, at least on the pseudotyped retroviral vector, the integrity of the virus lipidic envelope, suggested to be important for the virus integrity [ 32 ].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Gendrot and collaborators employed the IHUMI-3 strain for which genomic data are not available, thus making it difficult to establish the degree of widespread of the virus and its comparison with other strains. Our SPR data indicated that doxycycline did not interact with relevant binding sites of S or ACE2 proteins, as instead suggested by an in silico study [ 15 ]. It cannot be excluded that it may affect, at least on the pseudotyped retroviral vector, the integrity of the virus lipidic envelope, suggested to be important for the virus integrity [ 32 ].…”
Section: Discussionsupporting
confidence: 57%
“…In silico docking studies suggested a direct interaction of tetracyclines with the RBD, which can result in inhibition of the RBD–ACE2 complex [ 15 ] and reported their ability to inhibit 3CLpro [ 16 ], thus interfering with virus internalization and replication. This antiviral activity was confirmed in a study on Vero E6 cells infected with a clinically isolated SARS-CoV-2 strain (IHUMI-3) showing that doxycycline, at concentrations compatible with the circulating levels reached after oral or intravenous administration, inhibited virus entry and replication [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gendrot and collaborators employed the IHUMI-3 strain for which genomic data are not available thus making difficult to establish the degree of widespread of the virus and its comparison with other strains. Doxycycline did not interact with relevant binding sites of S or ACE2 proteins, as instead suggested by an in-silico study (14). It cannot be excluded that it may affect, at least on the pseudotyped retroviral vector, the integrity of the virus lipidic envelope, suggested to be important for the virus integrity (27).…”
Section: Discussionmentioning
confidence: 87%
“…In-silico docking studies suggested a direct interaction of tetracyclines with the RBD which can result in inhibition of the RBD-ACE2 complex (14), and reported their ability to inhibit 3CLpro (15), thus interfering with virus internalization and replication. This antiviral activity was confirmed in a study on Vero E6 cells infected with a clinically isolated SARS-CoV-2 strain (IHUMI-3) showing that doxycycline, at concentrations compatible with the circulating levels reached after oral or intravenous administration, inhibited virus entry and replication (16).…”
Section: Introductionmentioning
confidence: 99%
“…Tetracycline is also reported to inhibit the binding of the SARS-CoV-2 spike protein to angiotensinconverting enzyme 2 (ACE2) (3). Thus, infection of cells by SARS-CoV-2 may be inhibited.…”
mentioning
confidence: 99%